Clinical features of patients with rheumatic diseases and COVID-19 infection in Sarawak, Malaysia - Sharifah Aishah, Wan; Cheng, Lay Teh; Benjamin Sachdev, Manjit Singh; Yaw, Kiet Cheong; Seow, Lin Chuah; Ahmad Tirmizi, Jobli (BMJ, 2020)
We read with great interest the article by Ye et al1 describing the clinical features and outcomes of patients with rheumatic diseases and COVID-19 in Wuhan, China. It concluded that length of hospital stay and mortality were similar between patients with rheumatic diseases and non-rheumatic groups, while respiratory failure was more common in patients with rheumatic diseases infected with COVID-19. D’Silva et al2 and Zhao et al3 subsequently highlighted the differences of clinical severity and outcomes in their respective cohorts of patients with rheumatic diseases and COVID-19. Fredi et al4 presented data from northern Italy which supported an association of elderly age and the presence of comorbidities with a poor outcome of COVID-19 infection, rather than the type of rheumatic disease or background medications. The Global Rheumatology Alliance5has recently published data of characteristics associated with hospitalisation for COVID-19 among patients with rheumatic diseases. We would like to share the clinical course of COVID-19 among patients with rheumatic diseases in Sarawak.